The complete mitochondrial genome of Acrossocheilus beijiangensis (Cyprinidae, Barbinae). (1st November 2016) - Lin, Tingting; Li, Qiang; Shu, Hu; Yue, Lei; Lin, Jianfeng; Hou, Liping
Abstract: Acrossocheilus beijiangensis is a species of freshwater fish in the family Cyprinidae. In this study, the complete mitochondrial genome of A. beijiangensis has been determined using polymerase chain reaction technique. The genome is 16 600 bp in length, it includes 22 tRNA genes, 13 protein-coding genes, two rRNA genes, a D-loop control region, and another non-coding region called replication origin of Light strand (OL). The order of mitochondrial genes was found to be analogous to other vertebrates. The overall base composition of A. beijiangensis, mitochondrial DNA, was calculated and determined to consist of 30.6% A, 24.9% T, 28.1% C, and 16.3% G. Additionally it was found that most of the mitochondrial genes are encoded on the heavy strand except the NADH dehydrogenase subunit 6 (ND6) and eight tRNA genes. The availability of A. beijangesis mitogenome will provide basic data for the systematic categorization of Acrossocheilus sp ., as well as the phylogenetic analysis of Cyprinid fishes.